2019
DOI: 10.1371/journal.pone.0213343
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of the Japanese Moral Foundations Dictionary

Abstract: The Moral Foundations Dictionary (MFD) is a useful tool for applying the conceptual framework developed in Moral Foundations Theory and quantifying the moral meanings implicated in the linguistic information people convey. However, the applicability of the MFD is limited because it is available only in English. Translated versions of the MFD are therefore needed to study morality across various cultures, including non-Western cultures. The contribution of this paper is two-fold. We developed the first Japanese… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 24 publications
0
24
0
Order By: Relevance
“…Recently, Murayama and Miura (2019) determined the validity and reliability of the Japanese MFQ with large Japanese samples (855 Japanese participants in Study 1 and 470 in Study 2) and found that the five-factor model was the best fit. The Japanese MFQ has been used in previous research on morality conducted in Japan (e.g., Takamatsu and Takai, 2017;Matsuo et al, 2019). The Japanese MFQ consists of sentences that are rated on a Likert-type scale, ranging from 0 (not at all/almost never) to 5 (very much/almost always).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Murayama and Miura (2019) determined the validity and reliability of the Japanese MFQ with large Japanese samples (855 Japanese participants in Study 1 and 470 in Study 2) and found that the five-factor model was the best fit. The Japanese MFQ has been used in previous research on morality conducted in Japan (e.g., Takamatsu and Takai, 2017;Matsuo et al, 2019). The Japanese MFQ consists of sentences that are rated on a Likert-type scale, ranging from 0 (not at all/almost never) to 5 (very much/almost always).…”
Section: Methodsmentioning
confidence: 99%
“…The Japanese Version of the MFD Matsuo et al (2019) translated the original MFD, which contains 324 English words, into Japanese using a semi-automated method. The authors provided evidence of its validity by comparing the number of the J-MFD words for each moral foundation in the situations that participants described as each foundation being followed and violated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the English-centricity of NLP has been the focus of much recent criticism and emphasis (e.g., Bender & Friedman, 2018), and much of the resources for text analysis in psychology are exclusively in English or are translated from English (e.g., the Japanese MFD; Matsuo, Sasahara, Taguchi, & Karasawa, 2019). These findings cannot be generalized to non-English-speaking cultures.…”
Section: Limitationsmentioning
confidence: 99%
“…Combining these criteria, Table 1 lists the highly cited studies that repeatedly meet the inclusion criteria, including the following list of surveys and their respective publication citations. Athota et al 2019;Bespalov et al 2017;Boer and Fischer 2013;Cantarero et al 2018;Curry et al 2019;Dogruyol et al 2019;Du 2019;Feldman 2019;Graham et al 2012Graham et al , 2011Haidt 2013aHaidt , 2013bHaidt and Graham 2007;Joseph 2004, 2011;Haidt et al 1993;Hu 2017;Hu et al 2020;Iurino and Saucier 2020;Kim et al 2012;Kim and Kang 2013;Koleva et al 2016;Matsuo et al 2019;Mooijman et al 2018;Moreira et al 2019;Nechtelberger et al 2017;Nejat et al 2015;Niazi et al 2020;Nilsson and Erlandsson 2015;Ochoa et al 2016;Peker et al 2018;Purzycki et al 2018;Rahman 2015;Shim et al 2018;Shweder 1990;Shweder and Haidt 1993;Shweder et al 1997 Since the focus is on contemporary publications in the last decade, studies that originated before 2010 were included if a number of current publications continued to analyze the study's data within the 2010-2020 focus (e.g., WVS, ESS, EVS). However, studies that were primarily investigated prior to 2010, without numerous contemporary analyses were excluded.…”
Section: Systematic Phasementioning
confidence: 99%